SYNTHESIS AND CHARACTERIZATION OF MIXED LIGAND COMPLEXES OF SALICYLALDOXIME, DIMETHYLGLYOXIME AND BENZOIN WITH Mn (II) AND THEIR BIOLOGICAL ACTIVITY. - S. S.JADHAV; N.H.KOLHE; A.E.ATHARE (International Journal of Pharma and Bio Sciences, 2013)
The organic ligands contain nitrogen, oxygen and carbonyl and were used for preparation of Metal –Ligand chelated complexes. An ethanolic solution of salicylaldoxime, dimethylglyoxime and benzoin were reacted with aqueous solution of metal salts to give complex with symmetric ligands. Two different ligand solutions were mixed one after other in aqueous metal salt solution to give asymmetric ligand that is mixed ligand complexes having general formula [M(S)(D)] & [M(D)(B)] .The resulting product was found to be solid which have been characterized using FTIR spectrum which shows bands for characteristic frequencies in which –OH,-C=O,-C=N, C-O, M-O and M-N the groups are present. UV-Vis spectroscopy shows that nitrogen and oxygen of ligands donate the electron pair to metal and form the cheated complexes. Thermo Gravimetric Analysis (TGA) of all mixed ligand complexes was carried out to determine the procedural and decomposition temperatures. The temperature range in which decomposition occurs is in between 115oC-440oC. The magnetic properties were determined from Gouy balance method. The µeff. was found to be from 3.20 BM to 4.88BM as against the calculated 5.93BM value by using spin only formulae. It indicate that the hybridization of complexes is sp3d2 having octahedral geometry & is paramagnetic in nature. The complexes were checked for their biological activity by using E.Coli and B. subtilis bacteria. Only the mixed ligand complexes of benzoin and Dimethylglyoxime with Mn (II) were found to be biological active.